A Global Challenge : The Illegal Wildlife Trade Chain - Agarwal, Prashant (Journal of Commerce and Trade, 2015)
Illegal wildlife trade threatens key forest landscapes throughout the world. These practices decimate valuable resources and millions of livelihoods, and contribute to global warming. Illegal trade in wildlife is depriving developing economies of billions of dollars in lost revenues and development opportunities. Understanding the phenomenon requires a broad insight into the relationship between the environmental resources at stake, their legal and illegal exploitation, loopholes, as well as the scale and type of crimes committed. Due to the problem’s broad scale, a comprehensive approach is required. To curb the rise in environmental crime the response must involve legal responses, enforcement, legislation, regulation, environmental management, consumer and demand-reduction strategies, and alternative livelihood opportunities.